2021
DOI: 10.3390/biom11070972
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Kinase Inhibitor Midostaurin Improves Functional Neurological Recovery and Attenuates Inflammatory Changes Following Traumatic Cervical Spinal Cord Injury

Abstract: Traumatic spinal cord injury (SCI) impairs neuronal function and introduces a complex cascade of secondary pathologies that limit recovery. Despite decades of preclinical and clinical research, there is a shortage of efficacious treatment options to modulate the secondary response to injury. Protein kinases are crucial signaling molecules that mediate the secondary SCI-induced cellular response and present promising therapeutic targets. The objective of this study was to examine the safety and efficacy of mido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…NHP66 has a similar structure to human cortical bone, with marvelous toughness, stress strength, and fusion with bone [ 13 ]. Studies have shown that NHP66 can also form an antibacterial and anti-inflammatory biological scaffold with antimicrobial titanium, which has a certain adjuvant therapeutic effect on infected bone defects or osteomyelitis [ 14 ]. For short-track speed skaters, they need not only to restore the height of the injured vertebrae and reconstruct the normal sequence of cervical vertebrae but also more stable internal fixation and a higher rate of intervertebral fusion.…”
Section: Introductionmentioning
confidence: 99%
“…NHP66 has a similar structure to human cortical bone, with marvelous toughness, stress strength, and fusion with bone [ 13 ]. Studies have shown that NHP66 can also form an antibacterial and anti-inflammatory biological scaffold with antimicrobial titanium, which has a certain adjuvant therapeutic effect on infected bone defects or osteomyelitis [ 14 ]. For short-track speed skaters, they need not only to restore the height of the injured vertebrae and reconstruct the normal sequence of cervical vertebrae but also more stable internal fixation and a higher rate of intervertebral fusion.…”
Section: Introductionmentioning
confidence: 99%
“…However, kinase inhibitors are often non-specific; hence, there may be other off-target effects of TFP which we have not considered. For example, Midostaurin, a small-molecule inhibitor of multiple kinases such as PKC, caused a significant number of kinomic changes in a cervical SCI model [38]. Nonetheless, we showed that the inhibition of D2 and PKC increased spinal cord water content, demonstrating that the direct and specific inhibition of CaM and PKA is responsible for attenuating SCI-induced oedema after TFP treatment [20].…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, the proliferation of perivascular fibroblast-derived stromal cells, meningeal fibroblasts, and pericytes leads to scar formation and modifications within the spinal ECM [ 7 ]. Treatment strategies targeting these early processes can have a lasting effect on functional recovery and chronic preservation of neural tissue [ 5 , 34 ], hence the present study aimed to further investigate therapeutic targets during the early subacute phase of injury.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of traumatic SCI varies according to geographic location [ 2 ], but in the United States alone, it is estimated that there are approximately 17,900 new cases per year [ 3 , 4 ]. Traumatic SCI results from sudden mechanical damage to spinal neuronal, glial, and vascular cells due to an external force, and leads to a cascade of secondary molecular changes that further damage the spinal cord [ 5 ]. This secondary response is characterized mainly by early hypoxia, hemorrhage, and inflammation, which over-time results in cavitation and scar formation [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation